The Incidence of Herpes Zoster in a United States Administrative Database - Insinga, Ralph P (Blackwell Science Inc, 2005)
BACKGROUND: Few recent studies have reported data on the incidence of herpes zoster (HZ) in U.S. general clinical practice. OBJECTIVE: To estimate the age- and sex-specific incidence of HZ among U.S. health plan enrollees. DESIGN: Data for the years 2000 to 2001 were obtained from the Medstat MarketScan database, containing health insurance enrollment and claims data from over 4 million U.S. individuals. Incident HZ cases were identified through HZ diagnosis codes on health care claims. The burden of HZ among high-risk individuals with recent care for cancer, HIV, or transplantation was examined in sub-analyses. Overall incidence rates were age- and sex-adjusted to the 2000 U.S. population. PARTICIPANTS: MarketScan U.S. health plan enrollees of all ages. MEASUREMENTS AND MAIN RESULTS: We identified 9,152 incident cases of HZ (3.2 per 1,000 person-years) (95% confidence interval [CI], 3.1 to 3.2 per 1,000). Annual HZ rates per 1,000 person-years were higher among females (3.8) than males (2.6) (P<.0001). HZ rates rose sharply with age, and were highest among individuals over age 80 (10.9 per 1,000 person-years) (95% CI, 10.2 to 11.6). The incidence of HZ per 1,000 person-years among patients with evidence of recent care for transplantation, HIV infection, or cancer (10.3) was greater than for individuals without recent care for these conditions (3.0) (P<.0001). CONCLUSIONS: The overall incidence of HZ reported in the present study was found to be similar to rates observed in U.S. analyses conducted 10 to 20 years earlier, after age- and sex-standardizing estimates from all studies to the 2000 U.S. population. The higher rate of HZ in females compared with males contrasts with prior U.S. studies.